Compacted Laser-Induced Graphene with Bamboo-Like Carbon Nanotubes for Transformable Capacitive Energy Storage Electrodes - Hyeong, Seok Ki; Park, Mina; Kim, Seung Il; Park, Seoungwoong; Choi, Kwang Hun; Im, Min Ji; Kim, Nam Dong; Kim, Tae Wook; Lee, Sang Hyun; Park, Ji Won; Bae, Sukang; Lee, Jae Hyun; et al. (Advanced Materials Technologies, 2022)
Laser-induced graphene (LIG) has drawn attention for energy storage devices owing to its fascinating material properties as well as for its use in the effective production of porous structures. However, the low packing density of LIG, which is caused by macroscopic voids owing to rapid degassing during the instantaneous photothermal process, limits the improvement of device performance. Herein, the fabrication of compacted LIG composite is introduced, wherein, the unused voids are filled with bamboo-like carbon nanotubes (BCNTs). The BCNTs grown directly in the voids of LIG through chemical vapor deposition (CVD) method using Cu seeds as catalysts improve the electrical conductivity, chemical activity, and mechanical flexibility, while enhancing the spatial efficiency of the porous structure. Consequently, the fabricated composite film (denoted as BCNT:LIG/Cu) delivers an energy density of 1.87 μWh cm−2, which is ≈10 times higher than that of the LIG-based supercapacitor (0.19 μWh cm−2). Moreover, the BCNT:LIG/Cu film with a shape engineering pattern is assembled into a solid-state supercapacitor using a gel electrolyte (PVA-KOH), showing excellent electrochemical and mechanical stabilities under complex deformations. The proposed LIG-based densification strategy opens up opportunities for the development of energy devices for portable power supply in practical applications.
Keywords: Bamboo-like carbon nanotubes; Capacitive energy storage; Graphene-Cu; Laser induced; Laser-induced graphene; Packing density; Photothermal process; Porous graphene; Porous structures; Transformable energy storage; bamboo-like carbon nanotube; laser-induced graphene; porous graphene; supercapacitor; transformable energy storage